Combining the IAD and SES frameworks. Issue 1 (April 2019) - Cole, Daniel H.; Epstein, Graham; McGinnis, Michael D.
Elinor Ostrom's IAD (Institutional Analysis and Development) and SES (Social-Ecological Systems) frameworks are widely used by social scientists and policy analysts, but many applications fail to take full advantage of the potential utility of either framework. The IAD framework lacks detail regarding the specific variables that influence social interactions and neglects questions of asymmetric power and collective evaluation. The SES framework, meanwhile, supports detailed variable-oriented analyses of social-ecological systems, but rarely addresses the dynamic processes that lie at the heart of the IAD framework. We outline a Combined IAD-SES (CIS) Framework that remedies these problems by combining them in a format suited both to social-ecological systems and other policy settings. Institutional analysts using this combined framework should start their analysis by identifying a set of focal action situations, learning how the relevant collective and constitutional choice arenas shaped their structures, and then thinking deeply about the processes through which those conditions have been (or might be) changed. We demonstrate the potential utility of CIS by applying it to previous research on Maine's lobster fishery.